0.3-Volt Rail-to-Rail DDTA and Its Application in a Universal Filter and Quadrature Oscillator - Fabian Khateb; Montree Kumngern; Tomasz Kulej; Dalibor Biolek (Sensors, 2022)
@ 84.47 Hz input voltage. The slight modification of the filter yields a quadrature oscillator. The condition and the frequency of oscillation are orthogonally controllable. The frequency of oscillation can also be controlled electronically. The THD for a 67 Hz oscillation frequency was around 1.2%. The circuit is designed and simulated in a Cadence environment using 130 nm CMOS technology from United Microelectronics Corporation (UMC). The simulation results confirm the performance of the designed circuits.
Keywords: Analog and Mixed-Signal Circuit Design; Advancements in PLL and VCO Technologies; Neuroscience and Neural Engineering